PKM Kelompok Ibu-Ibu Nelayan Mengolah Ikan Jadi Bakso dan Abon di Lappa Kabupaten Sinjai - Amirullah Amirullah; Jumadi Jumadi; Muh Rasyid Ridha; Fitrah Widyawati; Dalilul Falihin (Universitas Negeri Makassar, 2024)
This service problem is carried out on a group of traditional fisherwomen in Lappa, Sinjai Regency. do not have skills in processing marine natural resources, the level of education level of traditional fisherwomen education level in Lappa, Sinjai Regency is very low.The solution offered is training conducted to women's groups related to with processed products which include; processing processing of sea fish into shredded meat, naget, meatballs, and other types of processed products such as making decorations with shellfish as the basic ingredients of natural potential in the region, as well as entrepreneurship training for mothers, especially in terms of entrepreneurship management. lauaran achieved by the ability of the target group to increase 90% related to the management of small businesses. ability of the target group increased by 90% related to the production of fish processing into shredded fish, naget, meatballs, and making ornaments from sea shells. Managerial skills of mothers of of traditional fishermen increased by 85%.